Financial Assistance for Euro Area Countries Affected by the Debt Crisis - Grabińska, Barbara (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The global crisis that reached Europe in 2008 has evolved from a financial crisis to a debt crisis. The problems in Greece, Ireland, Portugal, Spain and Cyprus turned out to be so severe that they could not be managed at the national level. These countries therefore asked for external assistance. The aim of the article is to describe the crisis-resolution mechanism and the attempts to provide stability to euro area countries through financial-assistance instruments. In view of the numerous controversies over the efficiency of financial-assistance programmes, methods of evaluating their success and failure are also discussed.